Control of as-cast microstructure morphology of high silicon electrical steels produced through a horizontal belt casting process simulator. (27th May 2020) - Slater, Carl; Ji, Mo; Bandi, Bharath; Davis, Claire
ABSTRACT: Increase in global electrification is driving the development of new electrical steels with improved performance, such as Fe–6Si suitable for high-frequency e-machines. Fe–6Si steel is difficult to cast and roll such that currently, the only commercial production is via downstream siliconisation to increase Si content. This paper explores the feasibility of casting ultra-high silicon electrical steels through a belt cast simulator and how the microstructure depends on casting parameters. Changes in the superheat, belt profile, belt coating and cast thickness have been considered and shows that microstructures from large columnar grains with a highly favourable {100} texture, to fine equiaxed random texture grains can be produced. It is also shown that casting to thicknesses of around 3.5 mm can be achieved such that a minimal amount of deformation is needed to produce the final product (around 0.1 mm thick), which will reduce the likelihood of cracking during rolling.